Tert-butylhydroquinone alleviates early brain injury and cognitive dysfunction after experimental subarachnoid hemorrhage: role of Keap1/Nrf2/ARE pathway. - Zhong Wang (Public Library of Science (PLoS), 2014)
Tert-butylhydroquinone (tBHQ), an Nrf2 activator, has demonstrated neuroprotection against brain trauma and ischemic stroke in vivo. However, little work has been done with respect to its effect on early brain injury (EBI) after subarachnoid hemorrhage (SAH). At the same time, as an oral medication, it may have extensive clinical applications for the treatment of SAH-induced cognitive dysfunction. This study was undertaken to evaluate the influence of tBHQ on EBI, secondary deficits of learning and memory, and the Keap1/Nrf2/ARE pathway in a rat SAH model. SD rats were divided into four groups: (1) Control group (n=40); (2) SAH group (n=40); (3) SAH+vehicle group (n=40); and (4) SAH+tBHQ group (n=40). All SAH animals were subjected to injection of autologous blood into the prechiasmatic cistern once in 20 s. In SAH+tBHQ group, tBHQ was administered via oral gavage at a dose of 12.5 mg/kg at 2 h, 12 h, 24 h, and 36 h after SAH. In the first set of experiments, brain samples were extracted and evaluated 48 h after SAH. In the second set of experiments, changes in cognition and memory were investigated in a Morris water maze. Results shows that administration of tBHQ after SAH significantly ameliorated EBI-related problems, such as brain edema, blood-brain barrier (BBB) impairment, clinical behavior deficits, cortical apoptosis, and neurodegeneration. Learning deficits induced by SAH was markedly alleviated after tBHQ therapy. Treatment with tBHQ markedly up-regulated the expression of Keap1, Nrf2, HO-1, NQO1, and GSTα1 after SAH. In conclusion, the administration of tBHQ abated the development of EBI and cognitive dysfunction in this SAH model. Its action was probably mediated by activation of the Keap1/Nrf2/ARE pathway.